(untitled) (Al-Academy, 2018)
This study deals with the intellectual representations whose intellectual systems are incarnated in the Jewish personality, which is considered one of the complex intellectual systems that has caused controversy throughout the ages because of the ambiguity due to the religious and psychological factors that were reflected directly and strongly on the intellectual structure of the Jewish community in general and the Jewish - Zionist personality in particular, in an attempt (to create new dimensions embodied by intellectual representations of a human nature embodied by what that - peaceful - religiously oppressed - psychologically and socially isolated character presents, because of the curse of the peoples of the world that was a cause for its isolation. The researcher, in this study, dealt with three sections:The first section: Dramatic characterThe second section: the intellectual dimension of the dramatic characterThe third section: Jewish character in dramaThe study was based on the analysis of the Munich film, which focuses on the idea of the national homeland of the Jews and the portrayal of the Jewish character with human dimensions that seek to achieve peaceful coexistence and rejection of the terrorist ideology practiced against them by the world in general and the Arabs in particular.